2013
DOI: 10.6061/clinics/2013(06)16
|View full text |Cite
|
Sign up to set email alerts
|

Importance of prostate-specific antigen (PSA) as a predictive factor for concordance between the Gleason scores of prostate biopsies and RADICAL prostatectomy specimens

Abstract: OBJECTIVE:To evaluate the concordance between the Gleason scores of prostate biopsies and radical prostatectomy specimens, thereby highlighting the importance of the prostate-specific antigen (PSA) level as a predictive factor of concordance.METHODS:We retrospectively analyzed 253 radical prostatectomy cases performed between 2006 and 2011. The patients were divided into 4 groups for the data analysis and dichotomized according to the preoperative PSA, <10 ng/mL and ≥10 ng/mL. A p-score <0.05 was considered si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 23 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…GS discrepancies resulting in upgrades and downgrades from biopsy to radical prostatectomy (RP) remain an important issue in clinical practice after 2005. The concordance between GS on biopsy and RP ranged from 28% to 70% before the 2005 ISUP consensus, and has ranged from 41% to 63% since 2005% . Although some found improved agreement between biopsy GS and RP GS after 2005, in some studies there was only marginal improvement .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GS discrepancies resulting in upgrades and downgrades from biopsy to radical prostatectomy (RP) remain an important issue in clinical practice after 2005. The concordance between GS on biopsy and RP ranged from 28% to 70% before the 2005 ISUP consensus, and has ranged from 41% to 63% since 2005% . Although some found improved agreement between biopsy GS and RP GS after 2005, in some studies there was only marginal improvement .…”
Section: Introductionmentioning
confidence: 99%
“…Although some found improved agreement between biopsy GS and RP GS after 2005, in some studies there was only marginal improvement . From 2005 to 2014 the reported rates of downgrading and upgrading were 5–21% and 22–47%, respectively . Importantly, the lack of concordance between the biopsy GS and RP GS can potentially impact under‐ and overtreatment.…”
Section: Introductionmentioning
confidence: 99%
“…However there was no significant correlation between mean PSA level and Gleason score of <7 (p>0.05). 12 Dobruch et al also found weak correlation of Gleason score of serum PSA in their study on 377 patients with LUTS who underwent TRUS guided prostatic biopsy. 10 In our study out of 16 patients who were biopsy proven prostate carcinoma, among 16 patients with biopsy proven adenocarcinoma, 1 (0.9%) patients had cT1c disease, whereas cT2 and cT3 were seen in 13 (12.8%) and 2 (1.98%) patients respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Digital rectal examination (DRE) and transrectal ultrasonography are a primary diagnostic tools having a low specificity and sensitivity 1,6 , and the transrectal biopsy is an essential factor for the confirmation of the diagnosis. 7 Histopathologic assessment can be further confirmed by the use of immunohistochemistry in select cases for the diagnosis and characterization of prostate cancer. 8 The prostate specific antigen (PSA) is a protein, which is produced by the cells of prostate gland and is nowadays widely used in the diagnosis and management of prostatic cancer.…”
Section: Introductionmentioning
confidence: 99%